Calculation Rational Rates Based on Unit Costs Compared to Kudungga Hospital Surgical Instalation Rates - Endah Dwi Setianingtyas; Ratno Adrianto; Iwan Muhamad Ramdan; Irfansyah Baharuddin Pakki; Iriyani Kamaruddin; Rahmat Bahtiar (Indonesian Journal of Global Health Research, 2025)
Hospitals that have carried out unit cost calculations can find out how much they are spending, so that the hospital can know if waste occurs. This is because the costs incurred by one hospital will be different from those incurred by another hospital, even though the hospital is in the same type of hospital. Apart from that, the results of unit cost calculations can also be used as a basis for decision making to improve hospital quality and quality. The aim of this research is to calculate rational rates for types of surgery using the multiple distribution method, then compare them with hospital rates for general surgery rates at the Central Surgical Installation of Kudungga Sangatta Regional Hospital. This study is a comparative descriptive quantitative analytical study to compare the rational rates of types of operations (special, special, major, major, and medium cito operations) in the general surgery group during the period of 2023 with the rates of general surgery operations at the Central Surgery Installation of Kudungga Sangatta Regional Hospital with a sample population of all 340 patients using BPJS insurance who received general surgery operations. The results of the research show that the rational rates obtained for special CITO operations are IDR 14,094,633, special operations IDR 12,383,431, large CITO operations IDR 5,262,904, large operations IDR 6,775,203, and medium operations IDR 3,858,857. Rational rates are higher than hospital rates, except for major CITO surgery rates. Therefore, when determining hospital rates, it is necessary to consider unit cost analysis so that hospital operational costs can be efficiently spent.